1990
DOI: 10.1523/jneurosci.10-03-01025.1990
|View full text |Cite
|
Sign up to set email alerts
|

A vasoactive intestinal peptide-like cotransmitter at cholinergic synapses between rat myenteric neurons in cell culture

Abstract: Intracellular recording and immunochemical techniques were used to study synaptic transmission between individual pairs of rat myenteric plexus neurons in cell culture. This report describes the synaptic connections made by “dual function” presynaptic neurons that evoked slow postsynaptic depolarizations (slow EPSPs) in the same neurons in which they also evoked fast nicotinic cholinergic EPSPs. The slow EPSPs occurred only when presynaptic neurons were stimulated at frequencies of 5 Hz or higher. During the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…Previous studies have shown that individual neurones in cell cultures prepared from rat myenteric plexus can evoke slow EPSPs in other neurones (Willard & Nishi, 1985 Willard, 1990). In this study, immunocytochemical staining has been used to demonstrate that subsets of myenteric neurones that evoke EPSPs contain immunoreactive SP.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Previous studies have shown that individual neurones in cell cultures prepared from rat myenteric plexus can evoke slow EPSPs in other neurones (Willard & Nishi, 1985 Willard, 1990). In this study, immunocytochemical staining has been used to demonstrate that subsets of myenteric neurones that evoke EPSPs contain immunoreactive SP.…”
Section: Introductionmentioning
confidence: 82%
“…Cultures of myenteric neurones were prepared as described by Nishi & Willard (1985) and Willard (1990) from tissue strips removed from the small intestines of 1-to 3-day-old rat pups (CD strain; Charles River) that had been killed by decapitation.…”
Section: Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these factors, vasoactive intestinal peptide (VIP), is found at a variety of nerve terminals throughout the nervous system, frequently colocalizes with ACh, and may function as a cholinergic cotransmitter (Gozes and Brenneman, 1989;Whittaker, 1989;Willard, 1990). Treatment of CG neurons with VIP increases ACh responses, but not nAChR surface levels, by increasing intracellular cAMP (Gurantz et al, 1994).…”
Section: Regulatory Signals That Mediate the Effects Of Synaptic Partmentioning
confidence: 99%